Pengaruh Media Wayang Bali Inovatif dalam Mempromosikan Pencegahan HIV/AIDS di Kabupaten Bangli - I Gst Gd Ngurah Kursista, Yayi Suryo Prabandari, Rendra Widyatama (Berita Kedokteran Masyarakat (BKM), 2009)
Background: HIV/AIDS still becomes a pandemic that attacked million of people in the world and the cases increasing every year including among household. This condition was possibly caused by the low of knowledge and perception of community regarding HIV/AIDS. Head of family is a target group of health promotion for HIV/ AIDS prevention. Health promotion with innovative Bali puppet media was expected could improve knowledge and perception of head of family in HIV/AIDS prevention.Objective: This research was aimed to find out the influence of health promotion through innovative Bali puppet media compared to speech method toward head of family in HIV/AIDS prevention effort.Method: This was a quasi experimental research that used equivalent control group design with pre test and post test. The sample was head of family in the sub district of Kintamani and Susut. The sample was selected purposively and the data was collected by using questionaire. Analysis was done by using independent t test, paired t test and descriptive. Indeed, the statistic was based on the significance level of p=0,05.Result: The method of innovative Bali puppet and speech had significant influence in knowledge improvement. After one month given health promotion on HIV/AIDS, there was an improvement on perception in the group of innovative Bali puppet which was better than speech group.Conclusion: Health promotion method by using innovative Bali puppet media and speech method could improve knowledge and perception of head of family in HIV/AIDS prevention, however innovative Bali puppet media which was high in improve knowledge and perception of head family in HIV/AIDS prevention.Keywords: innovative Bali puppet media, health promotion, HIV/AIDS prevention